Avaliação do efeito das variáveis de processo na descafeinização da erva-mate por extração com fluido supercrítico - Franceschini, Gustavo do Nascimento (2017)
The caffeine extraction process of yerba mate presents itself as an economically attractive activity, capable of generating two products with high market value, decaffeinated yerba mate, a differentiated product and natural caffeine, a compound with a growing demand in the current market. The purpose of this study was to evaluate the effect of the properties of plant material and the effect of process operating conditions in the caffeine removal from mate through supercritical extraction. To this objective, supercritical carbon dioxide extraction technology was used. The studied characteristics of the plant material were particle size, density and moisture content. After the optimum parameters were defined, the effect of the processing to which yerba mate is submitted was also evaluated, in three different stages: harvesting, zapecado and cancheamento. As for the operating conditions, it was assessed the influence of the porosity and the cosolvent content (ethanol) during the extraction process, with the pressure and operating temperature were set at optimum values for the removal of caffeine. Still, the effect of the mass ratio plant / solvent weight used was also studied. The extracts were analyzed by highperformance liquid chromatography. It was observed that increasing water content present in plant favored removal of caffeine, reaching a final concentration of 0.30% of caffeine (g / 100g), while the use of ethanol as cosolvent during the extraction process yielded in a final concentration of 0.03% (g / 100g) caffeine. For the processing, the zapecada sample presented the best results overall, both in yield of extract obtained and caffeine removal. Regarding the biological activity of the decaffeinated product, it was verified that the infusions of yerba mate decreased the cell viability of different cell lines of esophageal cancer and that this effect was independent of the concentration of caffeine present in the plant. Finally, the mathematical modeling of the extraction curve was performed in order to correlate the variables of the process with the experimental data.